A Critical Investigation of Consumer Response for Monetary and Non-monetary Promotions Across E-services. Issue 2 (December 2020) - Sharma, Ayushi; Wali, O. P.; Joshi, Rakesh Mohan
Monetary and non-monetary promotions are very evident in e-commerce. Consumer comes across them daily while making purchase decisions. This study brings in the perspective of how consumer leverages the two types of promotion when they choose to make their e-purchase. Study focuses on three service sectors (ordering food online, booking ride online and booking event tickets) and how consumer response differs across them for evaluating two categories of promotion. Consumer budget also plays an important role. It changes the consumer shopping orientation as well as the evaluation of promotion while making a purchase decision. Study also shows that gender play a significant role while evaluating monetary promotion; however, non-monetary promotions are no different for them. The findings of the study have implications for e-retailers to implement their promotional strategies more efficiently.